Financial Ratio Analysis: A Case Study of Chaturbhujeshwar Janta Multiple Campus Nepal - Ray, Ram Sudesh (Chaturbhujeshwar Academic Journal, 2024)
This study conducted a financial ratio analysis to analyze the financial health condition and operational performance of CJMC, a QAA-certified community campus in Harion, Sarlahi, Nepal. The study was based on secondary data, and data were accumulated from the audit report of fiscal years 2075/076 to 2079/080. The primary financial ratios examined are the administrative expense ratio, government reliance ratio, personal expense ratio, current ratio, and net margin ratio. The results indicate a decline in the administrative expense ratios, indicating the effectiveness of cost control. However, the government reliance ratio fluctuates substantially, posing a threat to financial stability due to the campus’s dependency on changeable government financing. The personal expense ratio is quite volatile, peaking at 90.89 percent in 2077/078 and indicating that labor expenditures have significantly exceeded the university budget. The current ratio has continuously fallen, dropping below 1.0 in recent years which indicates liquidity issues. The net margin ratio shows financial volatility, with significant deficits in 2076/077 and 2077/078, followed by a rebound in 2078/079 and 2079/080. The research concluded that the campus has worked to improve its financial position. Otherwise, it may continue to face issues such as declining enrollment and unstable regular revenue and should be dependent on local government assistance. Diversifying revenue streams, enhancing cash flow management, and optimizing personnel costs are all strategic recommendations for long-term financial sustainability.